2019
DOI: 10.1016/j.jhep.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare resource utilization and costs by disease severity in an insured national sample of US patients with chronic hepatitis B

Abstract: All-cause inpatient admissions (average stay 6-10 days) were more frequent in advanced liver disease states. Across all payers, patients with decompensated cirrhosis used the emergency department most (1.6-2.8 annual visits). HCC and liver transplant patients had highest proportion of outpatient hospital-based visits and annual visits. Advanced liver disease cohorts experienced 6-10Â higher costs than patients with compensated liver disease. Compensated liver disease patients with CHB incurred 3Â the cost of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 15 publications
(17 reference statements)
1
28
0
Order By: Relevance
“…for over 240 million de-identified patients in the US with Commercial and Medicare Supplemental insurance. The MarketScan database is commonly used for health economic studies of healthcare resource utilization and expenditures in insured populations including rare disease population such as patients with acute porphyria 9,21,22 .…”
Section: Datamentioning
confidence: 99%
“…for over 240 million de-identified patients in the US with Commercial and Medicare Supplemental insurance. The MarketScan database is commonly used for health economic studies of healthcare resource utilization and expenditures in insured populations including rare disease population such as patients with acute porphyria 9,21,22 .…”
Section: Datamentioning
confidence: 99%
“…Currently, there is no cure for CHB, so the emphasis of management is on prevention through vaccination. In fact, since 1991, when the United States adopted childhood vaccination programs, there has been a 68% decrease in the prevalence of HBV infection …”
Section: Adverse Effects Of Antiviral Therapymentioning
confidence: 99%
“…The annual incidence rate of cirrhosis among those with CHB is 1% to 2%, whereas among those with cirrhosis, the annual incidence rate of hepatocellular carcinoma is 3% to 5% . In addition to the high clinical burden with disease progression for those with CHB, there is also higher health care cost and resource utilization …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It might also be attributed to limited resources as well as increased cost of healthcare. Healthcare resource utilization and costs by different diseases shows a high economic burden highlighting need for taking some actions for decreasing costs [45][46][47]. The results of this review showed that CDSSs have the ability to improve laboratory tests utilization in some cases including hepatitis B virus, Clostridium Di cile, magnesium, B-Type natriuric peptide, TFT, ESR, and heparin-induced thrombocytopenia tests.…”
Section: Discussionmentioning
confidence: 91%